PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KREATIVITAS BELAJAR BIOLOGI SISWA DI SMA NEGERI 1 BARUMUN - Zulhandri Zulhandri; Sahlan Tuah; Yusni Atifah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
The problem in this study is the creation of learning the biology of students is still low in class XI IPA 2 SMA Negeri 1 Barumun, less varied learning models. The purpose of this research is to know the enhancement of student biology learning creativity through problem-based learning on tissue material on plants in class XI IPA 2 at SMA Negeri 1 Barumun year 2018-2019 lesson, through learning-based problems, the research approach used in this research is class action research. This research located at SMA Negeri 1 Barumun with the address of the cross-Riau road implemented after the approval letter of this research was issued. The subject is the class XI IPA 2 SMA Negeri 1 Barumun While the object is a test of learning creativity of students by using a problem-based learning model on tissue material in plants in class XI IPA 2 SMA Negeri 1 Barumun. The results of the creativity test on the I cycle gained an average of 72.25 with a percentage of 56.25% increase in cycle II by an average of 81.93 with compensation of  71.25%. Keywords: Creativity, learning outcomes, problem-based learning Model.